Modification of the analyzer on electrooptics for cooking oil quality testing. Issue 1 (July 2021) - Sugito, H; Utomo, G N; Firdausi, K S; Sumariyah, S; Khumaeni, A
Abstract: The importance of cooking oil for human consumption makes cooking oil needs to be aware of its quality. This research aims to design electrooptic devices by making modifications to the analyzer. The results of the ink design are used to test the quality of cooking oil. The method used in this tool is based on the electrooptical properties of cooking oil. Because the optical properties or the polarization angle used as an indicator of the quality of cooking oil is relatively very small, it is necessary to modify the analyzer on the existing electrooptics to avoid parallax errors and increase the effectiveness in measurement. Modifications were made by adding a stepper motor as an actuator, gears that intersect with certain radius ratios, and an ATMega 328P microcontroller for data controller and processing. in the cooking oil quality test, it can be distinguished oil that has expired and is still suitable for consumption based on the average value of the change in the polarization angle.